1977
DOI: 10.1002/app.1977.070210503
|View full text |Cite
|
Sign up to set email alerts
|

A semiempirical derivation of phase domain size in interpenetrating polymer networks

Abstract: SynopsisIn previous papers, interpenetrating polymer networks were shown to display a cellular structure.The phase domain size of polymer I1 was shown to depend inversely on the crosslink density of polymer I. The present paper presents a semiempirical derivation of equations which show quantitatively the dependence of the phase domain size of polymer I1 on the crosslinking density of polymer I, and also on the interfacial energy and the overall composition. If polymer I1 is linear, the dependence on the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
3

Year Published

1979
1979
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 11 publications
0
31
0
3
Order By: Relevance
“…4 The phase-separated structure of IPNs depends on both the thermodynamic miscibility of the constituent networks and the kinetic conditions of the crosslinking reaction. Sperling et al 5 found that an increase in crosslinking density leads to a decrease in the degree of phase separation in SBR-PS IPNs. In an SIPN, the crosslinking density of the first network is more important to morphology development than that of the second network.…”
Section: Introductionmentioning
confidence: 99%
“…4 The phase-separated structure of IPNs depends on both the thermodynamic miscibility of the constituent networks and the kinetic conditions of the crosslinking reaction. Sperling et al 5 found that an increase in crosslinking density leads to a decrease in the degree of phase separation in SBR-PS IPNs. In an SIPN, the crosslinking density of the first network is more important to morphology development than that of the second network.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological data showing that IPNs are highly heterogeneous structures allowed Sperling et al [72][73][74] to propose the mechanism of IPN formation called nucleation and growth. A thermodynamic theory of IPN morphology has been developed in [74].…”
Section: Nucleation and Growthmentioning
confidence: 99%
“…A thermodynamic theory of IPN morphology has been developed in [74]. Its main assumption is that there are two separate states of polymer I and polymer II separated one from another.…”
Section: Nucleation and Growthmentioning
confidence: 99%
See 2 more Smart Citations